2014
DOI: 10.1179/1432891714z.000000000835
|View full text |Cite
|
Sign up to set email alerts
|

Effect of process parameters on microstructures and properties of DZ125 superalloy solidified by LMC

Abstract: High thermal gradient in the interface region of melting and solidified metal during the unidirectional solidification has significant impact on the microstructures and mechanical properties of the castings. In this paper, DZ125 superalloy was solidified by directional equipment associated with liquid metal cooling medium of Ga-In alloy. Several process parameters have been chosen in order to understand the effect of thermal gradient on the castings. Comparing with traditional high rate solidification prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that during solidification of Ni-based superalloys, the formation of coarse eutectic (γ+γ′) can be inhibited by raising cooling rates [15][16][17] . However, this method is only applicable to small cross-section ingots [18] . Minor elements C, B and Zr are usually doped in Ni-based wrought superalloys for better mechanical properties [19][20][21][22] .…”
Section: Effect Of Zr On Solidification and Microstructure Of A Ni-based Superalloy With High Al And Ti Contentsmentioning
confidence: 99%
“…Studies have shown that during solidification of Ni-based superalloys, the formation of coarse eutectic (γ+γ′) can be inhibited by raising cooling rates [15][16][17] . However, this method is only applicable to small cross-section ingots [18] . Minor elements C, B and Zr are usually doped in Ni-based wrought superalloys for better mechanical properties [19][20][21][22] .…”
Section: Effect Of Zr On Solidification and Microstructure Of A Ni-based Superalloy With High Al And Ti Contentsmentioning
confidence: 99%
“…However, for the nickel-based superalloys with high Al and Ti content (generally Al þTi4 6 wt%), the hot cracking can be easily formed during high energy beam processing [7]. The typical instances include DZ4125 [8], Rene80 [9], Inconel 738LC [10], Inconel 713C [11] and AllVac718PLUS [12]. Previous study has shown that Inconel 738LC superalloy, which contained the considerable amount of Al and Ti (Al þTi 46 wt%), is susceptible to the cracking in the heat affected zone (HAZ) during LSF [13].…”
Section: Introductionmentioning
confidence: 99%